Self-Healing Polyurethane-Based Nanocomposites Modified with Carbon Fibres and Carbon Nanotubes - Szatkowski Piotr; Pielichowska Kinga; Blazewicz Stanislaw (Advances in Polymer Technology)
Self-healing polyurethanes (PUs) were synthesized as a matrix of nanocomposites containing two fibrous carbon components, i.e., functionalized carbon nanotubes (CNF-OH) and short carbon fibers (CF). Two types of PUs differing in the content of flexible chain segments (40% and 50%) were used. Changes in mechanical strength were analyzed to assess the ability to self-healing of PU-based matrix nanocomposites with experimentally introduced damage in the form of an incision. The healing process was activated by heating the damaged samples at 60°C, for 30 minutes. The addition of CNT-OH and CF caused a slight reduction in the self-healing ability of the nanocomposites as compared to the neat PUs. After heating to 60°C, the nanocomposites self-healed up to 72% of the initial strength of the undamaged samples. The introduction of fibrous components to the polymer matrix improved the thermal conductivity of nanocomposites and facilitated heat transfer from the environment to the interior of the samples, necessary to initiate self-healing. Low content of carbon components in the PU matrix, i.e., 3 wt% of CF and 2 wt% of CNF-OH increased the total work up to fracture of samples after healing by about 53%.